The Influence Of Mathematical Process Skills On The Character Of Cooperation In High Grades Of Acceleration And Debit Materials - Kamid, Kamid; Kurniawan, Dwi Agus; Perdana, Rahmat; Minarsih, Minarsih; Rohana, Siti; Ferdinan, Roy Andre; Alfiana, Rizki (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2023)
The aim of this research is to find out how mathematical process skills influence the cooperation of high class students on acceleration and discharge material. This type of research uses mixed methods with an explanatory design. The sample for this research was 18 high school students at 4 different elementary schools. The collection used a random sampling technique. The instruments used in this research are a questionnaire sheet and observation sheet with cooperative characters as basic indicators and mathematical process skills as integrated indicators. The data obtained were analyzed using descriptive statistics and using regression tests for cooperative characters and mathematical process skills. This study confirms that mathematical process skills have an impact on students' cooperative character. This is proven by a sig (2-failed) value < 0.05. It can be concluded from the results of the table that the four schools have a regression influence on mathematical process skills with a cooperative character on mathematics learning regarding measurement and discharge material.